2016
DOI: 10.1007/s12026-016-8843-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy and immunogenicity of switching from innovator to biosimilar infliximab in patients with spondyloarthritis: a 6-month real-life observational study

Abstract: Biosimilar infliximab (INX) was recently approved by the European Medicine Agency for the treatment of rheumatoid arthritis, ankylosing spondylitis (AS), Crohn's disease, ulcerative colitis, psoriatic arthritis (PsA), and psoriasis on the grounds that its pharmacokinetics, safety, and efficacy were comparable to those of innovator INX. The aim of this study was to investigate the real-life efficacy, safety, and immunogenicity of switching from innovator to biosimilar INX in patients with spondyloarthritis (SpA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 15 publications
1
35
0
1
Order By: Relevance
“…There was a need for additional medication to control increased disease activity after switching from originator to biosimilar infliximab in four of 83 patients with inflammatory bowel disease (IBD) [68] and in 13 of 28 patients undergoing chemotherapy and switching epoetins [77]; a significant increase in median C-reactive protein values (from 1.95 to 4.0 mg/L; P  < 0.05) and median pain scores (from 28.8 to 38.1 mm on a scale of 0–100; P  < 0.05) in patients with IBD switching from originator to biosimilar infliximab [43]; a significant increase in disease activity (mean Bath Ankylosing Spondylitis Activity Index, from 3.8 to 4.3; P  < 0.05) in patients with spondyloarthritis after switching to biosimilar infliximab [71]; a small, significant increase in total daily insulin dose (from 0.62 to 0.65 U/kg/day; P  < 0.05) in patients with type 1 or type 2 diabetes mellitus switched to a biosimilar insulin [87]; but a significant decrease (i.e. improvement) in duration of morning stiffness [median duration, from 7.2 to 5.8 (no units provided); P  = 0.02] in patients with arthritis switching from originator to biosimilar infliximab [47]. In the three remaining studies that included statistical analyses, IBD disease activity significantly improved in paediatric patients switched from originator to biosimilar infliximab ( P  < 0.05; actual values not reported) [66], but significantly worsened in adults who underwent a similar switch (median IBD-Control-8 score, from 11 to 14; P  < 0.05) [63], and primary failure was significantly lower in patients with IBD switched from originator to biosimilar infliximab than in patients switched from other biologics or who were treatment naïve (0 vs 11 and 10%, respectively; P  < 0.05) [50].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a need for additional medication to control increased disease activity after switching from originator to biosimilar infliximab in four of 83 patients with inflammatory bowel disease (IBD) [68] and in 13 of 28 patients undergoing chemotherapy and switching epoetins [77]; a significant increase in median C-reactive protein values (from 1.95 to 4.0 mg/L; P  < 0.05) and median pain scores (from 28.8 to 38.1 mm on a scale of 0–100; P  < 0.05) in patients with IBD switching from originator to biosimilar infliximab [43]; a significant increase in disease activity (mean Bath Ankylosing Spondylitis Activity Index, from 3.8 to 4.3; P  < 0.05) in patients with spondyloarthritis after switching to biosimilar infliximab [71]; a small, significant increase in total daily insulin dose (from 0.62 to 0.65 U/kg/day; P  < 0.05) in patients with type 1 or type 2 diabetes mellitus switched to a biosimilar insulin [87]; but a significant decrease (i.e. improvement) in duration of morning stiffness [median duration, from 7.2 to 5.8 (no units provided); P  = 0.02] in patients with arthritis switching from originator to biosimilar infliximab [47]. In the three remaining studies that included statistical analyses, IBD disease activity significantly improved in paediatric patients switched from originator to biosimilar infliximab ( P  < 0.05; actual values not reported) [66], but significantly worsened in adults who underwent a similar switch (median IBD-Control-8 score, from 11 to 14; P  < 0.05) [63], and primary failure was significantly lower in patients with IBD switched from originator to biosimilar infliximab than in patients switched from other biologics or who were treatment naïve (0 vs 11 and 10%, respectively; P  < 0.05) [50].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of safety data after switching, eight studies reported no concerns or similar safety profiles before and after switching [43, 44, 47, 50, 62, 63, 79, 87, 89], six studies reported no general safety data [45, 51, 72, 77, 83, 90], and 12 studies reported adverse events such as injection site pain, acute hypersensitivity reactions, rash and infusion reactions after switching (although most did not provide comparative data from before switching) [46, 48, 49, 52, 54, 58, 6568, 71, 88]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies seem to be reassuring in terms of efficacy maintenance and safety (9)(10)(11). However, in a recent report, of 23 patients with stable disease remission who were switched from re-IFX to bio-IFX, 7 experienced disease flare-ups after a mean interval of 2 months (12).…”
Section: Discussionmentioning
confidence: 99%
“…Patients from three rheumatology centers were switched to biosimilar infliximab and followed during 6 months. Biosimilars were found to be as effective as the innovator ones and with similar efficacy, and with no adverse events or the development of antidrug antibody [15]. Among the many immune-mediated diseases, the following were presented in different sessions.…”
Section: Immune-mediated Diseases and Mechanisms Of Inflammationmentioning
confidence: 99%